Seizure Semiology, EEG, and Imaging Findings in Epilepsy Secondary to Mitochondrial Disease - Fine, Anthony L.; Liebo, Greta; Gavrilova, Ralitza H.; Britton, Jeffrey W. (Frontiers in Neurology, 2021)
Background: Identification of an underlying mitochondrial disorder can be challenging due to the significant phenotypic variability between and within specific disorders. Epilepsy can be a presenting symptom with several mitochondrial disorders. In this study we evaluated clinical, electrophysiologic, and imaging features in patients with epilepsy and mitochondrial disorders to identify common features which could aid in earlier identification of a mitochondrial etiology. Methods: Retrospective case series from January 2011 through December 2019 at a tertiary referral center of patients with epilepsy and a genetically confirmed diagnosis of a mitochondrial disorder. One-hundred sixty-four patients were reviewed with twenty patients fulfilling inclusion criteria. Results: Twenty patients (14 females, 6 males) aged 0.5 to 61 years with epilepsy and genetically confirmed mitochondrial disorders were identified. Status epilepticus occurred in 15 patients, with focal status in 13 patients, including nine with visual features. Abnormalities over the posterior head cerebral regions were seen in 66% of ictal recordings and 44% of imaging studies. All patients were on nutraceutical supplementation with no significant change in disease progression seen. At last follow-up 8 patients were deceased and the remainder had moderate to severe disability. Discussion: In this series of patients with epilepsy and mitochondrial disorders, we found increased propensity for seizures arising from the posterior head cerebral regions. Over time EEG and imaging abnormalities increasingly occurred over the posterior head cerebral regions. Focal seizures and focal status epilepticus with visual symptoms were common. Additional study is needed on nutraceutical supplementation in mitochondrial disorders.